Presenteeism and noise perception at work: a cross-sectional study using association analysis - Tavares, Renata da Silva Cardoso Rocha; Silva, Luiz Felipe; Muniz Júnior, Jorge (São Paulo Medical Journal, 2023)
BACKGROUND: Presenteeism refers to the presence of a worker at work with reduced performance due to illness, and it is a common public health problem. Exposure to noise during production processes brings risk to workers’ health. OBJECTIVE: To analyze the health profile of workers in the automotive industry and identify the association between noise perception and presenteeism among workers in the Brazilian automotive industry. DESIGN AND SETTING: This was a cross-sectional study utilizing a case study design analyzing the automotive industry in the interior of São Paulo state, Brazil. METHODS: This study included 306 workers using the Presenteeism Work Limitations Questionnaire protocol. Multiple logistic regression was used for data analysis. RESULTS: Male workers with reports of headache, tension, and limited well-being at work, having perceived that noise exposure interferes with productivity, showed a positive association with the occurrence of presenteeism. Physical demand had the highest score in terms of interfering with the presenteeism index. CONCLUSION: Workers’ perceptions of noise were associated with presenteeism.